DAMPAK BANTUAN LANGSUNG TUNAI DANA DESA (BLT-DD) TERHADAP PENGELUARAN RUMAH TANGGA MISKIN DI DESA PELAGA PADA MASA PANDEMI COVID-19 - Onibala, Jesika; Setyari, Ni Putu Wiwin (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.06.TAHUN.2023, 2023)
The purpose of this study was to analyze the effect of the Village Fund Direct Assistance (BLT-DD), Work Status, and Income simultaneously and partially on the Expenditure of Poor Households in Pelaga Village, Petang District during the Covid-19 Pandemic. This research was conducted in Pelaga Village, Petang District, Badung Regency, Bali Province. The population in this study were poor households who were beneficiaries of BLT-DD in Pelaga Village. The number of samples is 130 beneficiary households. The sampling technique is a non-probability sampling technique, namely by accidental sampling. The data analysis technique used was multiple linear regression analysis. The results showed that the Village Fund Direct Cash Assistance (BLT-DD), Work Status, and Income simultaneously affected the Expenditures of Poor Households in Pelaga Village, Petang Subdistrict during the Covid-19 Pandemic. Direct Village Fund Cash Assistance (BLT-DD), Working Status, and Income partially have a positive effect on Poor Household Expenditures in Pelaga Village, Evening District during the Covid-19 Pandemic.